Materials for civil and construction engineers - Mamlouk, Michael S.; Zaniewski, John P. (Pearson Education Limited, 2018)
For courses in Civil Engineering Materials, Construction Materials, and Construction Methods & Materials offered in Civil, Environmental, or Construction engineering departments. Civil and Construction Engineering Materials: Properties, Uses, and Evaluations Materials for Civil and Construction Engineers helps students understand and select the materials involved in supporting the infrastructure needs of society--from buildings, to water and treatment distribution systems, to dams, highways, and airport pavements. By gaining a deep understanding of material behavior and the material selection